PENGARUH ENDOSER DIAN SASTRO DALAM IKLAN PERAWATAN RAMBUT LâOREAL DI TELEVISI TERHADAP MINAT BELI - Sandy, Novena (Universitas Prof. Dr. Moestopo (Beragama), 2012)
LâOreal using television advertising is to informing, to persuading, to reminding, and to adding value of the product. Celebrity endorsement stategy that LâOreal used is to getting power attention. Dian Sastro as celebrity endorser LâOreal has credibility, attractiveness dan visibility. Using Dian Sastro as a endorser is to increase student buying interest LâOreal product. Stimulus-Respond theory as grand theory in this research with model VisCap and hierarchy of effects for the operational concept. Celebrity endorsement in advertising is influences students buying interest.